Problem behaviour in adolescent boys with fragile X syndrome: relative prevalence, frequency and severity. Issue 12 (11th October 2016) - Hall, S. S.; Barnett, R. P.; Hustyi, K. M.
Abstract: Background: A large proportion of boys with fragile X syndrome (FXS), the most common known inherited form of intellectual disability (ID), exhibit problem behaviours (e.g. aggression, self‐injury, property destruction and stereotypy) that can negatively impact the health and safety of others as well as the individual concerned. However, data are limited concerning the relative prevalence, frequency and severity of problem behaviours exhibited by boys with FXS compared with those by boys with mixed‐aetiology ID who also exhibit problem behaviours. Method: As part of a larger study on problem behaviour, we obtained survey data on 85 adolescent boys with FXS and 155 age‐matched boys with mixed‐aetiology ID who exhibited at least one form of problem behaviour. Results: For boys with FXS, stereotypy was reported to be more prevalent ( χ 2 = 4.52, P = 0.012), self‐injury was reported to more frequent ( U = 2525, P = 0.010) and aggression was reported to be less severe ( U = 4176, P = 0.029) than for boys with mixed‐aetiology ID. Ratings of aggression and property destruction were highly correlated in each group in terms of both frequency and severity ( r = 0.60 to 0.71). Examination of the data by age indicated that the relative frequency of self‐injury decreased with age in boys with FXS ( χ 2 = 8.29, P = 0.040). Conclusions: Taken together, these results refine and extend previous studies concerning the specificity of the behavioural phenotype in FXS and indicate that specific forms of problem behaviour shown by boys with FXS appear to differ from those exhibited by boys with mixed‐aetiology ID in terms of prevalence, frequency and severity. Studies employing more objective measures of frequency and severity, including direct observations, are needed to confirm these findings.